x-3y= -13

4x +2y=4

Take the first equation and solve for x:

x - 3y = -13

x = -13 + 3y

Now, substitute that into the second equation:

4x + 2y = 4

4(-13 + 3y) + 2y = 4

-52 + 12y + 2y = 4

Add 52 to both sides:

12y + 2y = 56

14y = 56

y = 4

Now, substitute y = 4 into the first equation:

x - 3(4) = -13

x - 12 = -13

x = -1

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up